Perancangan Sistem Absensi Menggunakan Qr-Code Berbasis Web di Kantor Pemerintah Desa Palatta - Nova Liswanty; Tri Wahyuni Pattola; Bustamin B; Basri Basri (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
The development of information technology encourages government agencies to switch from manual systems to digital systems that are more efficient and accurate. One important aspect of office administration is recording the absence of village officials, which is often done conventionally so it is prone to errors, data manipulation, and takes longer in the recapitulation process. Based on these problems, this research designs and implements a Qr-Code based attendance system at the Palatta Village Government Office. The design of this system is to provide a faster, more accurate and transparent attendance solution by utilizing Qr-Code technology which is integrated into a web-based application. The system is built with main features such as user login, Qr-Code scanning, attendance history, as well as an admin dashboard to manage data and generate reports. The results of implementation and testing using the Black Box method show that all functions run as required. Testing on users also shows that the system is easy to use, speeds up the attendance process, and helps admins in monitoring and recapitulating data. Thus, this Qr-Code attendance system is suitable to be implemented as a substitute for manual methods to increase work efficiency and discipline in the village office environment.